Facial Emotion Recognition in Schizophrenia: The Impact of Gender - Erol, Almıla (Korean Neuropsychiatric Association, 2013)
OBJECTIVE: Previous studies reported gender differences for facial emotion recognition in healthy people, with women performing better than men. Few studies that examined gender differences for facial emotion recognition in schizophrenia brought out inconsistent findings. The aim of this study is to investigate gender differences for facial emotion identification and discrimination abilities in patients with schizophrenia. METHODS: 35 female and 35 male patients with schizophrenia, along with 35 female and 35 male healthy controls were included in the study. All the subjects were evaluated with Facial Emotion Identification Test (FEIT), Facial Emotion Discrimination Test (FEDT), and Benton Facial Recognition Test (BFRT). Patients' psychopathological symptoms were rated by means of the Positive and Negative Syndrome Scale (PANSS). RESULTS: Male patients performed significantly worse than female patients on FEIT total, and negative scores. Male controls performed significantly worse than female controls on FEIT total and negative scores. On all tasks, female patients performed comparable with controls. Male patients performed significantly worse than controls on FEIT, and FEDT. CONCLUSION: Women with schizophrenia outperformed men for facial emotion recognition ability in a pattern that is similar with the healthy controls. It could be claimed that male patients with schizophrenia need special consideration for emotion perception deficits.